THE DETERMINANTS OF SYSTEMATIC RISK: INTERNATIONAL EVIDENCE FROM THE MACRO-FINANCE INTERFACE - ARFAOUI, Mongi; ABAOUB, Ezzeddine (Journal of Advanced Studies in Finance; Vol 1 No 2 (2010): JASF Volume I Issue 2 Winter 2010, 2010)
This paper aims to shed light on the determinants of systematic risk in the global macro-finance interface. We estimate a time-varying two-factor ICAPM, using weekly equity returns and MSCI market-capitalisation weighted basket of foreign currencies. We follow a two-step estimation procedure; in the first step, the timevarying betas and alphas are estimated using a GARCH (1,1) specification model. In the second step, the estimated betas and alphas are regressed on annual macroeconomic and financial variables using a panel approach. We find a significant exposure of country returns to non-systematic risk and to world market systematic risk. The significant exposure is defined by the dynamics of local risk factors as well as by global risk factors. As for the value added of the paper, we confirm the rise of global risk factors and the interferences between idiosyncratic and common factors. Moreover, specification tests enable as to verify the suitability of the selected variables and corroborate the mild-segmentation hypothesis. Our findings provide a potential usefulness for portfolio managers and for domestic governors aiming to improve their attractiveness indices.